Potential Impact of Populations Drift on Botrytis Occurrence and Resistance to Multi- and Single-Site Fungicides in Florida Southern Highbush Blueberry Fields - Amiri, A (Plant disease, 2018)
Incidence of blossom blight and Botrytis fruit rot (BFR), caused by Botrytis cinerea, on two southern highbush blueberry cultivars was evaluated in several blueberry fields grown in the vicinity (BB-Str(+)) or not (BB-Str(-)) of strawberry fields in central Florida. Blossom blight and BFR incidence were higher in BB-Str(+) fields in 2014 and significantly higher in 2015 compared to BB-Str(-) fields. In total, 613 B. cinerea isolates (i.e., 181 and 432 isolates from BB-Str(-) and BB-Str(+) fields, respectively) were collected. The isolates were evaluated for sensitivity to eight single-site and one multisite fungicides using a spore germination and a germ tube elongation assay. Overall, 5, 15, 24, 28, 54, and 93% of isolates collected from BB-Str(-) were resistant to penthiopyrad, cyprodinil, boscalid, fenhexamid, pyraclostrobin, and thiophanate-methyl, respectively. Respective resistance frequencies in BB-Str(+) isolates were 10, 30, 65, 66, 89, and 99%. Resistance frequencies for all fungicides were always higher in BB-Str(+) fields compared to BB-Str(-) fields. Isolates exhibiting resistance to six or five fungicides simultaneously were predominant (50 to 70%) in blueberry fields regardless if they were grown in the vicinity of strawberry fields or not. Among 308 and 305 B. cinerea isolates tested in 2014 and 2015, 41.8 and 47.1%, respectively, showed reduced sensitivity to the multisite fungicide captan. The lower label rate of captan applied preventively did not control isolates with reduced sensitivity on detached blueberry fruit. These findings suggest a potential population flow between strawberry and blueberry fields that may impact blossom blight and gray mold development in blueberry fields. The relatively lower fungicide input applied to blueberry fields compared with strawberry fields seems to be sufficient to select for resistance and multiple-resistant phenotypes in B. cinerea populations in blueberry